ADAM8 in macrophages exacerbates sepsis-induced cardiomyopathy by impeding efferocytosis - Ji, Zhenjun; Guo, Jiaqi; Wang, Mi; Zhang, Rui; Dong, Rong; Sheng, Zulong; Zuo, Pengfei; Zhu, Kongbo; Li, Yongjun; Yao, Yuyu; He, Hongliang; Ma, Genshan (Frontiers in Immunology, 2025)
IntroductionSepsis-induced cardiomyopathy (SICM) is a life-threatening complication characterized by acute cardiac dysfunction during sepsis., and macrophages play a crucial role in SICM pathogenesis. ADAM8 has been implicated in inflammation-driven diseases, yet its role in SICM remains uncharted.MethodsMouse models of SICM were established using lipopolysaccharide (LPS) injection and cecal ligation and puncture (CLP). Macrophage-specific ADAM8 knockout (CKO) mice were generated. RNA transcriptome sequencing was conducted on left ventricular tissues sourced from ADAM8 CKO mice, as well as on RAW264.7 cell lines that were treated with both ADAM8 knockdown (KD) lentivirus and LPS.ResultsHere, we demonstrate that ADAM8 expression is significantly upregulated in cardiac macrophages of SICM mice using single-cell transcriptomics and immunofluorescence. Macrophage-specific ADAM8 CKO mice exhibited preserved cardiac function, reduced myocardial injury markers, attenuated apoptosis (decreased Bax/Bcl2 ratio), and enhanced survival in both LPS-induced and CLP sepsis models. Transcriptomic analysis revealed downregulation of cytokine-cytokine receptor pathways in CKO hearts, suggesting diminished inflammatory responses. Mechanistically, ADAM8 deficiency promoted macrophage efferocytosis by increasing phagocytic receptors (MerTK) while reducing soluble Mer (sMer) generation. Conversely, sMer administration abolished the cardioprotective effects in CKO mice, exacerbating cardiac dysfunction and mortality.ConclusionsOur findings identify ADAM8 as a critical regulator of macrophage-mediated inflammation and impaired macrophage efferocytosis in SICM. Targeting ADAM8 or its downstream effectors may represent a novel therapeutic strategy for sepsis-induced cardiac complications.